Sand and dust storms: underrated natural hazards. Issue 2 (29th November 2018) - Middleton, Nick; Tozer, Peter; Tozer, Brenton
Abstract : Sand and dust storms (SDS) are wind erosion events typically associated with dryland regions, although they can occur in most environments and their impacts are frequently experienced outside drylands because desert dust haze often is transported great distances. SDS represent hazards to society in numerous ways, yet they do not feature prominently in the disasters literature. This paper considers SDS in a hazard context by examining their ramifications in economic, physical, and social terms, with a focus on agriculture, health, transport, utilities, households, and the commercial and manufacturing sector. There are few assessments of the economic consequences of SDS and those studies that have been conducted lack consistency in data collection methods and analysis. SDS do not result in the significant damage to infrastructure usually associated with many disasters, but the cumulative effects on society can be significant because SDS occur more commonly than most other types of natural hazard.